Successful treatment of peritoneal dialysis for two patients with refractory nephrotic syndrome and acute kidney injury: a case report - Yu, Le; Cheng, Shuiqin; Zhang, Man; Zhou, Tingting; Chen, Yunmin; Zhang, Zhihong; Yu, Yusheng (Frontiers in Medicine, 2023)
Two patients with refractory nephrotic syndrome were treated with peritoneal dialysis (PD) for diuretic resistance, anasarca and acute kidney injury. Following PD, their fluid overload was promptly alleviated, accompanied by an increase in urine volume and an improvement in renal function. PD as an adjuvant approach enabled them to resume corticosteroids and immunosuppressive agents. Eventually, both patients could be withdrawn from PD and achieved remission of proteinuria.